Electrical energy from CO2 emissions by direct gas feeding in capacitive cells. (1st October 2019) - Legrand, L.; Schaetzle, O.; Tedesco, M.; Hamelers, H.V.M.
Abstract: This work demonstrates the possibility to harvest electrical power from CO2 emissions by feeding CO2 and air gas directly into a capacitive cell. Hamelers et al. previously showed, that the available mixing energy of CO2 emitted into the air can be converted into electricity, but at high energy costs for gas-sparging in the process. In the present work, electrical power is generated by feeding the gas directly into the capacitive cell. We investigated three different cell designs (namely, "conventional", "flow-by(wire)", and "flow-by(flat)"), by changing both electrode and cell geometry. The flow-by(flat), inspired from fuel cell design, showed the best performance thanks to a high membrane potential (≈190 mV), which is the highest value so far reported from CO2 and air. A maximum membrane permselectivity between CO2 and air of 90% was obtained, i.e., almost double of values reported in previous studies. On the contrary, the "conventional" cell design gave poor performance due to non-optimal gas flow in the cell. We highlight the importance of water management and internal electrical resistance, to indicate directions for future developments of the technology. Graphical abstract: Image 1 Highlights: Electrical power can be generated from capacitive cells by feeding CO2 gas. The highest membrane potential was obtained into a PEM fuel cell design. The highest power density was obtained with the PEM fuel cell designs. Future research direction should focus on reducing the cell electrical resistance.